Production of chicken feather protein by Keratinase from Bacillus subtilis G8 for corncob silage production - Chayatip Suttiniyom (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
This study aimed to investigate the utilization of partially digested chicken feather by bacterial keratinase as a protein source for the improvement of the protein content in corncob silage. Comparison of chicken feather digestions by Bacillus subtilis G8 culture and crude keratinase was investigated. Digestion by crude keratinase released the soluble protein corresponding with the enzyme quantities used. The maximum soluble protein released by crude keratinase were 27 and 23% by weight from milled chicken feather (MCF) and un-milled chicken feather (UCF), whereas bacterial digestion released 51 and 43% from MCF and UCF, respectively. Partially digestion by bacterial culture was selected as the appropriate process based on total crude protein remaining, practicability and economic reasons. Using bacterial digested chicken feather (BDCF) as a protein source for corncob silage (CS) by mixing with 5, 10 and 15% BDCF resulted in silage treatment; CS-BDCF-5%, CS-BDCF-10% and CS-BDCF-15%. Proximate analysis of CS-BDCF revealed that addition of BDCF clearly increased the crude protein. Crude protein of 33.46%, 14.12% and 25.02% was obtained from CS-BDCF-15%, CS-BDCF-5% and CS-BDCF-10%, respectively. Gas production values from in vitro digestibility test of all CS-BDCF treatments were not different significantly at 24 hours, while in sacco digestibility test of CS-BDCF-15% showed the highest value of dry matter degradation. Feeding corncob silage supplemented with commercial concentrates Betagro 004S (CS-C) and CS-BDCF-15% on dairy cows showed that the average milk productivity of cows fed with CS-C was 7.2 kg/day which was significantly higher (P<0.05) than that of CS-BDCF-15% feeding which was only 5.4 kg/day. However, the average body weight gain of dairy cows after being fed by CS-BDCF-15% for 21 days increased to 35 kg while that of dairy cow fed with CS-C increased only 2.5 kg. The CS-BDCF-15% supplemented with essential minerals for milk production which is cheap and self-prepared might be able to be used for replacing the expensive commercial concentrates for dairy cows.